1990
DOI: 10.1128/aem.56.4.1179-1181.1990
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene degradation by two independent aromatic-degrading pathways in Alcaligenes eutrophus JMP134

Abstract: The bacterium Alcaligenes eutrophus JMP134(pJP4) degrades trichloroethylene (TCE) by a chromosomal phenol-dependent pathway and by the plasmid-encoded 2,4-dichlorophenoxyacetic acid pathway. The two pathways were independent and exhibited different rates of removal and capacities for quantity of TCE removed. The phenol-dependent pathway was more rapid (0.2 versus 0.06 nmol of TCE removed per min per mg of protein) and consumed all detectable TCE. The 2,4-dichlorophenoxyacetic acid-dependent pathway removed 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…A mutant strain of JMP134 grows with 2,4-dichlorophenol and with 4-chloro-2-methylphenol [ 121. Trichloroethylene degradation mediated by aromatic catabolic pathways in strain JMP134 has also been reported [13]. In the present work, we further explore the degradative abilities of A. eutrophus JMP134, by growing it in cultures containing chlorophenols as a sole carbon and energy source.…”
Section: Introductionmentioning
confidence: 75%
“…A mutant strain of JMP134 grows with 2,4-dichlorophenol and with 4-chloro-2-methylphenol [ 121. Trichloroethylene degradation mediated by aromatic catabolic pathways in strain JMP134 has also been reported [13]. In the present work, we further explore the degradative abilities of A. eutrophus JMP134, by growing it in cultures containing chlorophenols as a sole carbon and energy source.…”
Section: Introductionmentioning
confidence: 75%
“…Under methanogenic conditions, degradation was found to be relatively slow and mostly resulted in the accumulation of vinyl chloride, which is even more toxic (2,4,10,35,36). Laboratory studies have shown that TCE can be transformed aerobically by several oxygenase-producing bacterial cultures, including toluene-oxidizing strains (12,23,37,41), the ammonia-oxidizer Nitrosomonas europaea (1,34), and a propane-oxidizing Mycobacterium vaccae (38).…”
mentioning
confidence: 99%
“…In all cases examined so far, the active microorganisms contain catabolic oxygenases with relaxed substrate specificities which catalyze a fortuitous oxygenation of TCE upon being stimulated with their respective substrates (43). Such microorganisms include methanotrophs (1,9,13,14,16,21,30,37), propane oxidizers (41), ethylene oxidizers (13), toluene, phenol, or cresol oxidizers (10,12,26,27,28,42), 2,4dichlorophenoxyacetic acid oxidizers (12), and ammonia oxidizers (2,38).…”
mentioning
confidence: 99%